Late embryogenesis abundant proteins protect human hepatoma cells during acute desiccation - Li, Shumin (National Academy of Sciences, 2012)
Expression of late embryogenesis abundant (LEA) proteins is highly correlated with desiccation tolerance in anhydrobiotic animals, selected land plants, and bacteria. Genes encoding two LEA proteins, one localized to the cytoplasm/nucleus (AfrLEA2) and one targeted to mitochondria (AfrLEA3m), were stably transfected into human HepG2 cells. A trehalose transporter was used for intracellular loading of this disaccharide. Cells were rapidly and uniformly desiccated to low water content (<0.12 g H(2)O/g dry weight) with a recently developed spin-drying technique. Immediately on rehydration, control cells without LEA proteins or trehalose exhibited 0% membrane integrity, compared with 98% in cells loaded with trehalose and expressing AfrLEA2 or AfrLEA3m; surprisingly, AfrLEA3m without trehalose conferred 94% protection. Cell proliferation across 7 d showed an 18-fold increase for cells dried with AfrLEA3m and trehalose, compared with 27-fold for nondried controls. LEA proteins dramatically enhance desiccation tolerance in mammalian cells and offer the opportunity for engineering biostability in the dried state.